Deaf Community Cultural Wealth in Community College Students. (12th June 2020) - Johnson, Serena; Stapleton, Lissa; Berrett, Bryan
Abstract: Deaf students are members of a linguistic and cultural minority whose background and experiences provide a unique backdrop for the navigation of higher education. Using the framework of Deaf community cultural wealth, this study examines the experiences of Deaf students in community college and their utilization of various forms of capital. Findings showed that they exhibited instances of resistant, navigational, social, and familial capital in accessing and persisting in higher education.